The physical and developmental outcomes of children whose mothers are substance abusers: Analysis of associated factors and the impact of early intervention - Cheng, Anna Wai Fun; Chan, Hin Biu; Ip, Lai Sheung; Wan, Katy Kit Ying; Yu, Ellen Lok Man; Chiu, Wa Keung; Chung, Pui Hong; Yeoh, Eng Kiong (Frontiers in Pediatrics, 2022)
Background/objectives: Maternal illicit drug use is associated with negative physical and developmental outcomes of their born children. We aim to find out the incidence of different developmental problems in a cohort of Chinese children born to drug-abusing mothers, compare the physical health and developmental outcomes of the subjects recruited in the Integrated Program to the Comprehensive Child Development Service (CCDS) and to study the potential factors on their associations. Methods: A retrospective longitudinal cohort study with frequent clinical assessments of the children’s physical and developmental outcomes in a HKSAR’s regional hospital since birth until 5 years old. 123 children in Integrated Program were compared with 214 children in CCDS between 1 January 2008 to 28 February 2019. Cox-regression analysis was performed to determine the possible factors associated with the developmental outcomes. Results: Developmental delay was detected in 129 children (38.9%). CCDS group has significantly higher incidence of cognitive delay (p =<0.001), language delay (p =<0.001), motor delay (p =<0.001), social delay (p =0.002) and global delay (p =0.002). On Cox multivariable regression analysis, integrated program (HRadj 0.53, 95% C. I. 0.34-0.84), social support (HRadj 0.45, 95% C.I. 0.25-0.80) and maternal abstinence from drug use up to 2-year post-delivery (HRadj 0.62, 95% C.I. 0.40-0.95) were significant protective factors while male gender (HRadj 1.73, 95% C.I. 1.18-2.54) was a significant risk factor. Conclusions CCDS achieves to early engage drug-abusing expectant mothers at pregnancy and an early integrated program with multidisciplinary collaboration was an independent factor in improving these vulnerable children’s developmental outcomes.